2005
DOI: 10.1111/j.1538-7836.2004.01029.x
|View full text |Cite
|
Sign up to set email alerts
|

A collaborative study to establish the 7th International Standard for Factor VIII Concentrate

Abstract: To cite this article: Raut S., Bevan S., Hubbard A. R., Sands D., Barrowcliffe T. W. A collaborative study to establish the 7th International Standard for Factor VIII Concentrate. J Thromb Haemost 2005; 3: 119-26.Summary. A candidate concentrate, preparation N (99/678), was assayed and calibrated, as a potential replacement, against four established factor (F) VIII concentrate standards: the current WHO 6th International Standard (IS) (97/616), the previous 5th IS (88/640), the Mega 1 standard and Ph. Eur. BRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…A positive correlation was soon reported for solvent/detergent and heat treatments of the pdFVIII concentrates and inhibitory incidence in PUPs 30, 31. Biochemical investigations evidenced that new epitopes might form at the FVIII light chain C2‐domain level upon solvent/detergent and pasteurization treatment 32, 33. Although inhibitory antibodies developed by PUPs have been shown to target both the A2 domain of the HCh, and the A3 and C2 domains of the light chain, so far only the latter have attracted the main deal of investigative efforts 10, 32, 33.…”
Section: Discussionmentioning
confidence: 96%
“…A positive correlation was soon reported for solvent/detergent and heat treatments of the pdFVIII concentrates and inhibitory incidence in PUPs 30, 31. Biochemical investigations evidenced that new epitopes might form at the FVIII light chain C2‐domain level upon solvent/detergent and pasteurization treatment 32, 33. Although inhibitory antibodies developed by PUPs have been shown to target both the A2 domain of the HCh, and the A3 and C2 domains of the light chain, so far only the latter have attracted the main deal of investigative efforts 10, 32, 33.…”
Section: Discussionmentioning
confidence: 96%
“…However, there have been unforeseen accidents after some products were introduced to the market: After the introduction of two F VIII concentrates, unexpected development of inhibitors in previously treated patients occurred [12, 16, 17], resulting in the withdrawal of these products from the market. Some work was done to explain the origin of these unexpected side effects, unfortunately with limited success [12, 31]. It was shown that inhibitory antibodies were directed against the C2 domain in the light chain of the F VIII [32], but the peptide(s) responsible for antibody formation could not be conclusively determined.…”
Section: Discussionmentioning
confidence: 99%
“…Barrowcliffe et al [33] proposed that the purification process and virus inactivation, specifically heating, may expose new F VIII immunogenic epitopes. This hypothesis was examined further by Raut et al [31], Josic et al [12] and Saenko et al [34] using different chromatographic and electrophoretic methods, combined with surface plasmon resonance (SPR). From the analysis of potentially immunogenic, double virus inactivated F VIII concentrates, they found that some batches showed definitive evidence of elevated F VIII hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The potency of FXIII activity in pool N ranged from 87% to 111% (with a lower estimate of 69% from only one laboratory); this variation is hence much less than that observed for some other factors involved in hemostasis and thrombosis, such as a 2-fold range for FVIII [15,18]. The degree of variation in levels of FXIII antigen (A 2 B 2 complex) in the normal plasma pools (pool N) was similarly low as compared to that of the activity levels, ranging from 73% to 116%.…”
Section: Discussionmentioning
confidence: 99%